REVIEW: POTENSI MANFAAT APLIKASI GREEN ROOF - Widyastuti Kusuma Wardhani; Ika Rahmawati Suyanto; Sekar Arum Azzahra (Jurnal Environmental Science, 2022)
ABSTRACTRecently, The construction industry is growing rapidly in the world, including in Indonesia. The construction of high-rise buildings, industry, and housing certainly has an impact on the environment, one of which is the lack of rain catchment areas. The green building concept is expected to reduce energy consumption significantly through several methods of passive design and active design without sacrificing comfort and productivity due to energy savings. One solution to support the concept of green building is the application of green roofs in buildings. Green roof is a building construction where there is a planting medium and vegetation on the roof. The most important green roof capability is the ability to withstand and hold rainwater, especially in urban areas and reduce energy consumption. This study provides an overview of  the differences between extensive and intensive types of green roofs, the potential benefits of green roof applications on water quantity and quality, environmental impacts, opportunities and challenges of green roof applications, and economic benefits. Based on this positive aspect, it can be concluded that green roof is one of solution to reduce the environmental impact of buildings, save money, and save water reserves.